Antibody-dependent CD56+ T cell responses are functionally impaired in long-term HIV-1 infection. Issue 1 (December 2016) - Fan, Xueying; Zhu, Liyan; Liang, Hua; Xie, Zhe; Huang, Xiangbo; Wang, Shuo; Shen, Tao
Abstract Background Antibody-dependent cellular cytotoxicity (ADCC), which mainly mediated by natural killer (NK) cells, may play a critical role in slowing human immunodeficiency virus type-1 (HIV-1) disease progression and protecting from HIV-1 infection. Besides classic NK cells, CD56+ T cells also have some NK cell-like properties, such as the large granular lymphocyte morphology and the capacity to destroy NK-sensitive target cells. However, little is known about the potentials of antibody-dependent CD56+ T cell responses and the association between antibody-dependent CD56+ T cell responses and HIV-1 disease progression. Results In the present study, we showed evidences that, in addition to NK cells, CD56+ T cells could generate degranulation upon CD16 cross-linking.Ex vivo study showed that FcγRIII (CD16)-mediated CD56+ T cell responses were distinctly induced by IgG antibody-bound P815 cells. Comparatively, CD56− T cells and invariant NKT (CD3+ 6B11+) failed to induce antibody-dependent activation. Antibody-dependent CD56+ T cell responses were mainly ascribed to CD4/CD8 double negative subset and were functionally impaired in long-term HIV-1-infected former plasma donors, regardless of hepatitis C virus (HCV) coinfection status. Also, CD56+ T cell-mediated HIV-1-specific antibody-dependent responses were declined in men who have sex with men with HIV-1 infection over 3 years. Finally, we showed that matrix metalloprotease (MMP) inhibitor GM6001 could partially restored antibody-dependent CD56+ T cell responses of chronic HIV-1-infected subjects. Conclusions Our results suggested that CD56+ T cells could mediate ADCC responses and the responses were impaired in chronic HIV-1 infection.